Internalization Of Values In The Perspective Of Islamic Educational Philosophy - 'Aini, Khoirun Nisa Nur; Nurhuda, Abid Nurhuda; Huda, Ali Anhar Syi’bul (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Humans as God's creatures are designed to have goals and directions in life that are not created just like that, but duties and responsibilities must be carried out. In the view of education, humans are learning beings and the learning process includes various aspects and values that live and continue to develop until the end of life. Therefore, this article seeks to examine the process of value internalization viewed from the perspective of Islamic education as a whole. Articles written using a qualitative approach with the method of literature study and data analysis are described descriptively. The results of the study explain that the internalization of values can occur with education by the human himself or with assistance from other people as external parties. The stages of value internalization are carried out in three stages: value transformation, value transaction, and transinternalization. As for the values instilled, namely the values of ma'rifatullah, Abdullah, akhlakul karimah towards oneself (gentle, holding back anger, sincere, and competing in goodness), towards the family (birrul walidain, living, etc.), towards others (helping each other, not doing damage that can harm other people, etc.), national character, religious character.